Exploring the Digital Creative Product Design of Luoshan Shadow Based on Non-Fungible Tokens - Taotao, Xu; Musdi, Shanat (Paradigm Academic Press, 2023)
The popularity of Non-fungible Tokens is reshaping the Internet, digital assets and content. Many cultural sectorsworldwide have switched and proposed using NFT technology to enhance the liquidity of financialised art assets. Numerous companies are trying to take advantage of the rapid growth of the NFT markets to increase their competitiveness. Although digital artwork provides numerous technical advantages, few design practices areavailable for Luoshan Shadow’s NFT virtual creative products. This study aimed to investigate the factorsinfluencing the digital design of the Luoshan shadow by NFT technology. We conducted a thematic analysis of the comments and suggestions given by designers and non-geneticists. Data of 185 designers, consumers, andnon-geneticists indicated the main concerning themes; i) copyright and security issues; ii) innovation of art formand content; iii) new presentation, and iv) benefits from Non-fungible Tokens technology. These findings mayprovide experience for Luoshan shadow art to start the layout of digital creative design in the context of themuch-needed NFT market and to organically combine its digital derivatives with physical derivatives to achievejoint development.